Achieving optimal output consensus for discrete‐time linear multi‐agent systems with disturbance rejection. Issue 5 (24th December 2020) - Tang, Yutao; Zhu, Hao; Lv, Xiaoyong
Abstract: This paper studies an optimal output consensus problem for discrete‐time linear multi‐agent systems subject to external disturbances. Each agent is assigned with a local cost function which is known only to itself. Distributed protocols are to be designed to guarantee an output consensus for these high‐order agents and meanwhile minimize the aggregate cost as the sum of these local costs. To overcome the difficulties brought by high‐order dynamics and external disturbances, an embedded design is developed and a distributed rule to solve this problem is constructively present. The proposed control includes three terms: an optimal signal generator under a directed information graph, an observer‐based compensator to reject these disturbances, and a reference tracking controller for these linear agents. It is shown to solve the formulated problem with some mild assumptions. A numerical example is also provided to illustrate the effectiveness of our proposed distributed control laws.